Use of research methods in the process of pulmonary rehabilitation and physical therapy of persons with chronic obstructive pulmonary disease (review of clinical guidelines) - Тимрук-Скоропад, Катерина (Slobozhanskyi Herald of Science and Sport, 2018)
Kateryna Tymruk-Skoropad To date, the analysis of research methods and indicators on the basis of which the assessment of important areas of the physical, functional and psychoemotional state of patients with chronic obstructive pulmonary disease (COPD) at different stages of physical therapy is relevant. Purpose: to analyze and systematize recommendations on the use of research methods in the process of pulmonary rehabilitation and physical therapy in chronic obstructive pulmonary disease. Material & Methods: the available clinical guidelines for the diagnosis, treatment and pulmonary rehabilitation of patients with COPD are available. 13 clinical guidelines were analyzed. Results: selected research guidelines and categories were evaluated in selected clinical guidelines: diagnostic criteria, criteria for participation of patients in the pulmonary rehabilitation program, prognostic criteria, and selection criteria for pulmonary rehabilitation and physical therapy strategies, effectiveness markers. In clinical guidelines, the methods of research that recommend the evaluation of patients with COPD in the treatment and recovery process are grouped as follows: research methods and indicators of the functional state of the respiratory and cardiovascular system, estimates of the level of dyspnea, quality of life and the manifestation of COPD symptoms, the level of physical performance and integrated performance. Conclusion: most recommendations on the use of methods for studying patients with COPD are justified for diagnosis, prediction and selection of the strategy of drug treatment and oxygen therapy. Most of the recommendations are not sufficiently focused on using research methods and indicators as prognostic criteria and markers of the current and long-term effectiveness of physical therapy. Groups of research methods and indicators have been identified, with the help of which it is recommended to evaluate patients with COPD at the stages of diagnosis, patient selection, predicting the course of the disease, choosing a strategy of the pulmonary rehabilitation program and evaluating its effectiveness.